In-frame mutation in rice TEOSINTE BRANCHED1 (OsTB1) improves productivity under phosphorus deficiency. (May 2023) - Ishizaki, Takuma; Ueda, Yoshiaki; Takai, Toshiyuki; Maruyama, Kyonoshin; Tsujimoto, Yasuhiro
Abstract: Tillering is an important trait in rice productivity. We introduced mutations into the coding region of rice TEOSINTE BRANCHED1 ( OsTB1 ), which is a negative regulator of tillering, using CRISPR/Cas9. The frameshift mutants exhibited substantially enhanced tillering and produced 3.5 times more panicles than the non-mutated plants at maturity. This enhanced tillering resulted in increased spikelet number; however, grain yields did not increase due to substantially reduced filled grain rate and 1, 000-grain weight. In contrast, in-frame mutations in OsTB1 had the effect of slightly increasing tiller numbers, and the in-frame mutants had 40% more panicles than non-mutated plants. The grain yield of in-frame mutants also did not increase on nutrient-rich soil; however, under phosphorus-deficient conditions, where tillering is constrained, the in-frame mutants gave a significantly higher grain yield than non-mutated plants due to higher spikelet number and maintained filled grain rate. Rice grassy tiller1 ( OsGT1 )/ OsHox12, which is directly regulated by OsTB1 to suppress tillering, was moderately down-regulated in in-frame mutants, suggesting that OsTB1 with the in-frame mutation shows partial function of intact OsTB1 in regulating OsGT1 / OsHox12 . We propose that mildly enhanced tillering by in-frame mutation of OsTB1 can improve grain yield under low phosphorus conditions. Highlights: In-frame mutants for OsTB1 have slightly more tillers than non-mutated plants. OsTB1 with the in-frame mutation shows partial function in regulating OsGT1 / OsHox12 . The in-frame mutants give a higher grain yield under phosphorus-deficiency.